2014
DOI: 10.1371/journal.pntd.0002900
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Active Trachoma and Ocular Chlamydia trachomatis Infection in Treatment-Naïve Trachoma-Hyperendemic Communities of the Bijagós Archipelago, Guinea Bissau

Abstract: BackgroundTrachoma, caused by ocular infection with Chlamydia trachomatis, is hyperendemic on the Bijagós Archipelago of Guinea Bissau. An understanding of the risk factors associated with active trachoma and infection on these remote and isolated islands, which are atypical of trachoma-endemic environments described elsewhere, is crucial to the implementation of trachoma elimination strategies.Methodology/Principal FindingsA cross-sectional population-based trachoma prevalence survey was conducted on four isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 43 publications
8
85
2
2
Order By: Relevance
“…Younger children have been associated with higher odds of trachoma in many previous studies. 1719 In addition, open defecation is thought to increase infection transmission by providing an ecological niche for eye-seeking flies known to carry C. trachomatis . 20,21 Trachoma has been associated with altitude before, 21 but the finding in these surveys of a lower odds of trachoma at high (≥2500m) altitudes is difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…Younger children have been associated with higher odds of trachoma in many previous studies. 1719 In addition, open defecation is thought to increase infection transmission by providing an ecological niche for eye-seeking flies known to carry C. trachomatis . 20,21 Trachoma has been associated with altitude before, 21 but the finding in these surveys of a lower odds of trachoma at high (≥2500m) altitudes is difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…We have found, as others have, that not all TF cases were positive for chlamydia, which was expected because follicles take a long time to clear once infection is gone. [8][9][10] Finding evidence for infection in the areas with highest prevalence of trachoma does suggest that there are still pockets of true trachoma in these areas. Most villages even in the sub-districts with trachoma, had access to water and functional latrines.…”
Section: Discussionmentioning
confidence: 99%
“…At present, C. trachomatis is divided into serotypes A-L, which can cause conjunctivitis, reproductive-tract infection, venereal granuloma, neonatal pneumonia, active arthritis and other diseases. Trachoma is closely associated with serotypes A, B, Ba, and C (Last et al, 2014;Ishak et al, 2015). C. trachomatis remains an epidemic in various countries, and Canada is the only high-income country with a trachoma prevalence of >5% (Shattock et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…C. trachomatis remains an epidemic in various countries, and Canada is the only high-income country with a trachoma prevalence of >5% (Shattock et al, 2015). Active trachoma exists in a number of areas in Asia and Africa and other developing countries (Last et al, 2014;King et al, 2013;Nigusie et al, 2015;Burton et al, 2010), and a great number of studies have shown C. trachomatis serotypes differ across regions. For 8 .…”
Section: Discussionmentioning
confidence: 99%